Integration of meta-analysis and network pharmacology analysis to investigate the pharmacological mechanisms of traditional Chinese medicine in the treatment of hepatocellular carcinoma - Jie Lin; Huaijuan Guo; Hanjiao Qin; Xuewen Zhang; Jiyao Sheng (Frontiers in Pharmacology, 2024)
Background: This study will explore the therapeutic value of traditional Chinese medicine (TCM) in Hepatocellular Carcinoma (HCC) through meta-analysis, combined with network pharmacology analysis.Methods: The results of randomized controlled trials on TCM and HCC were retrieved and summarized from multiple databases. The effective active com-pounds and target genes of the high-frequency TCM were obtained using the TCMSP database, and disease targets of HCC were acquired through the public disease database. The network pharmacology analysis was used to get the core genes and investigate the potential oncogenic molecular mechanism.Results: A total of 14 meta-analysis studies with 1,831 patients suggested that therapy combined TCM is associated with better clinical efficacy and survival prognosis, as well as avoiding many adverse events. A total of 156 compounds, 247 herbal target genes and 36 core genes were identified. The function analysis suggested above genes may participate development in HCC through regulating some pathways, such as HIF-1 pathway and PD-L1 immune-related pathway.Conclusion: TCM, as a novel, safe, and effective multi-mechanism therapy, holds greater value in the treatment of HCC.